Microsatellite polymorphism in the P1 promoter region of the IGF-1 gene is associated with endometrial cancer - KWASNIEWSKI, WOJCIECH (Mol Med Rep, 2016)
Endometrial carcinoma (EC) is the most common type of gynecological malignancy. Studies have demonstrated that the insulin growth factor (IGF) pathway is implicated in the development of endometrial tumors and that the serum levels of IGF-1 are affected by estrogen. Most EC cells with high microsatellite instability (MSI-H) accumulate mutations at a microsatellite sequence in the IGF-1 gene. The present study investigated the CA repeat polymorphism in the P1 promoter region of the IGF-1 gene among Caucasian females with endometrial hyperplasia, EC and healthy control subjects, whose blood serum and surgical tissue specimens were analyzed. Differences or correlations between the analyzed parameters [serum levels of IGF-1 and IGF binding protein (IGFBP)-1 and IGFBP-3 as well as estrogens among the polymorphisms] were verified using the χ(2), Mann-Whitney U, Kruskal-Wallis or Spearman's rank correlation tests. A PCR amplification and DNA sequencing analysis was used for identification of (CA)(n) repeats in the P1 region of IGF-1. ELISA was used to determine the blood serum levels of IGF-1, IGFBP-1, IGFBP-3 and estrogens. Furthermore, IGF-1 was assessed in endometrial tissues by immunohistochemical analysis. The present study indicated no statistically significant differences between serum levels of IGF-1, IGFBP-1, IGFBP-3 and estrone, estriol and estradiol in the control and study groups. A significant correlation was identified between the IGF-1 levels and estrone levels in the MSI-H polymorphism (r=−0.41, P=0.012) as well as a highly negative correlation between IGF-1 levels and the estradiol levels in the MSI-H polymorphism (r=−0.6, P=0.002). Genotypes without the 19 CA allele were predominantly found in EC. Furthermore, statistical analysis indicated that the number of IGF-1-expressing cells was significantly elevated in MSI-H type 18-20 (P= 0.0072), MSI-L type 19-20 (P=0.025) and microsatellite-stable MSS type 19-19 (P=0.024) compared with those in the MSI-H 20-20 genotype. The present study suggested that it is rather likely that the polymorphisms in the IGF-1 promoter are associated with EC in Caucasian females with regard to its development. In the present study, polymorphisms of the IGF-1 promoter may have been introduced during the genesis of EC and contributed to it by leading to aberrant expression of IGF-1.